If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 4) = 6r Reorder the terms: 2(4 + x) = 6r (4 * 2 + x * 2) = 6r (8 + 2x) = 6r Solving 8 + 2x = 6r Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 2x = -8 + 6r Combine like terms: 8 + -8 = 0 0 + 2x = -8 + 6r 2x = -8 + 6r Divide each side by '2'. x = -4 + 3r Simplifying x = -4 + 3r
| 2n^2=7-2n | | 80=4x-40 | | 9b^2+6-3b-3-1b= | | 8(-2+3k)=-88 | | xya=y-x | | Q=k-c/x | | Log(1-x)-log(4+x)=1 | | -v/22 | | 4z+3=19-z | | -3(2+x)=6+2(x+1) | | 3x=7x-23 | | g(x)=2+6 | | 3x+12+2x+17=119 | | 5x+7=4x+15 | | p=6-.05(84) | | .375y=9 | | 6-4(3x-2)=10 | | 3z-1=137 | | an=5+.2(n-1) | | 36=4(x+1) | | 3n-5=8n-45 | | 3m2/3=7 | | x+73=x+133 | | axy=y-x | | -3(u-3)=4u+37 | | 8a+2-6+2a= | | 30+1x=15+3x | | 16+8q-4q+4=24 | | 7a+4=3a-4 | | (3p-7)(p+2)=0 | | 44=11x+33 | | x+(10+x)=46 |